TRANSFORMATIONAL LEADERSHIP OF DAYAH: EMPOWERMENT OF DAYAH COMMUNITY IN DEVELOPING TOTAL QUALITY MANAGEMENT - Almuhajir Almuhajir; Jumat Barus (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:This study aims to explain the transformational leadership of Dayah in empowering the Dayah community, which is focused on empowering the quality of teungku, santri, and administrative personnel for the development of Total Quality Management (QTM). The research method used was library research with a transformational leadership approach to educational institutions. Data sources consisted of books, journals, and other literacy sources related to Dayah educational institutions and transformational leadership. Data analysis used was content analysis by determining, describing, and interpreting the data. The result indicated that to empower teungku quality, Dayah leaders carry out the management, guidance and development of all teungku in the intellectual, spiritual, emotional and social dimensions. To empower the quality of students, Dayah leaders organize all activities related to the students, from input to output, with a series of cognitive, affective, and psychomotor activities. Empowerment of administrative personnel, Dayah leaders take steps to develop self-potential, fostering and increasing performance productivity, including scientific, loyal, skilled, and evaluating their performance to be measured.Abstrak:Penelitian ini bertujuan untuk menjelaskan kepemimpinan transformasional Dayah dalam pemberdayaan masyarakat Dayah yang difokuskan pada pemberdayaan mutu teungku, santri, dan tenaga administrasi untuk pengembangan Total Quality Management (QTM). Metode penelitian yang digunakan adalah penelitian kepustakaan dengan pendekatan kepemimpinan transformasional pada lembaga pendidikan. Sumber data terdiri dari buku, jurnal, dan sumber literasi lainnya yang terkait dengan lembaga pendidikan Dayah dan kepemimpinan transformasional. Analisis data yang digunakan adalah content analysis dengan menentukan, mendeskripsikan, dan menginterpretasikan data. Hasil dari penelitian ini menunjukkan bahwa dalam memberdayakan mutu teungku, pimpinan Dayah melakukan pengelolaan, pembinaan, dan pengembangan terhadap seluruh teungku dalam dimensi intelektual, spiritual, emosional, dan social. Untuk memberdayakan mutu santri, pimpinan Dayah melakukan penataan segala aktivitas yang berkaitan dengan santri mulai dari input sampai dengan out put dengan serangkaian aktivitas cognitif, afektif, dan psikomotorik. Untuk memberdayakan tenaga administrasi, pimpinan Dayah melakukan langkah-langkah dengan usaha pengembangan potensi diri, pembinaan dan peningkatkan produktivitas kinerja yang meliputi keilmuan, loyal, terampil, dan mengevaluasi kinerjanya agar dapat terukur.